2005
DOI: 10.1002/ejic.200400444
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Investigation of Palladium(II) Complexes with Phenanthroline Ligands: A Molecular Mechanics Approach

Abstract: Specific force field parameters have been derived through an optimisation procedure based on crystal structure data to describe the geometry of Pd II -phenanthroline complexes. The X-ray structure of [Pd(CH 3 )(3-sBu-phen) 2 ][OTf] is also reported. Molecular mechanics calculations show that intramolecular steric interactions yield severe distortions from a square-planar geometry of the metal atom, both in bischelated [Pd(3-R-phen) 2 ] 2+ and monochelated [Pd(CH 3 )(3-Rphen) 2 ] + complexes. A complete stereoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The formation of the Pd species attached to a pair of pyridinic nitrogen sites is also in line with the ability of palladium to form chelate complexes with N-containing organic ligands: for example, with phenanthroline containing a pair of pyridinic type nitrogen atoms. The structure of some complexes of Pd with this ligand is well studied. These complexes were used as homogeneous catalysts for different reactions. Thus, recently it was shown that complexes of some noble metals and iron with phenanthroline type ligands are active in the conversion of CO 2 to formate species and in the dehydrogenation of formic acid .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the Pd species attached to a pair of pyridinic nitrogen sites is also in line with the ability of palladium to form chelate complexes with N-containing organic ligands: for example, with phenanthroline containing a pair of pyridinic type nitrogen atoms. The structure of some complexes of Pd with this ligand is well studied. These complexes were used as homogeneous catalysts for different reactions. Thus, recently it was shown that complexes of some noble metals and iron with phenanthroline type ligands are active in the conversion of CO 2 to formate species and in the dehydrogenation of formic acid .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The structure of some complexes of Pd with this ligand is well studied. [48][49][50] These complexes were used as homogeneous catalysts for different reactions. Thus, recently it was shown that complexes of some noble metals 51 and iron 52 with phenanthroline type ligands are active in conversion of CO 2 to formate species 51 and in dehydrogenation of formic acid.…”
mentioning
confidence: 99%
“…For the intermolecular and intramolecular interactions, a general AMBER force field was used in combination with CH and CH 2 united atom parameters from a reoptimized united atom force field . For Pd atoms, we used parameters from the literature . For the ligand atomic charges, we used restrained electrostatic potential (RESP) charges, obtained using ab initio molecular orbital calculations with the B3LYP/6-31G(d) level in the Gaussian03 program…”
Section: Methodsmentioning
confidence: 99%
“…34 For Pd atoms, we used parameters from the literature. 35 For the ligand atomic charges, we used restrained electrostatic potential (RESP) charges, 36 obtained using ab initio molecular orbital calculations with the B3LYP/6-31G(d) level in the Gaussian03 program. 37 Trajectories were produced using the MD program GRO-MACS (version 4.0.7) 38 with a modified nonbonded interaction routine to employ the WCA potential described above.…”
Section: Methodsmentioning
confidence: 99%
“…Corresponding data for a PdAN(pyridyl) linkage does [20]. Since the CuAN(amido) bond stretch force constant (201.2 kcal/mol Å A For 2, a similar set of alterations in the optimized structure compared to the original crystal structure (Fig.…”
Section: Molecular Mechanis Calculationsmentioning
confidence: 97%